2013
DOI: 10.4244/eijv9i8a152
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs of young interventional cardiologists: the EAPCI Young survey

Abstract: The survey underlines the need to fill a gap in order to address the needs of young interventional cardiologists. It may serve as a starting point for developing educational initiatives targeted at young interventional cardiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…For recent years, only few data are available on the needs of early-career cardiologists 3,4 and needs for the changing paradigm in cardiology training. 5 Moreover, there is no specific report on the gaps in training in arrhythmology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For recent years, only few data are available on the needs of early-career cardiologists 3,4 and needs for the changing paradigm in cardiology training. 5 Moreover, there is no specific report on the gaps in training in arrhythmology.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first survey exploring the education background, self-assessed confidence in arrhythmia management and residual training needs of Italian early-career cardiologists. For recent years, only few data are available on the needs of early-career cardiologists 3,4 and needs for the changing paradigm in cardiology training 5 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different perspectives among men and women towards the quality of the research mentorship they are offered have not been reported before. [ 10 , 11 , 14 ] Thus, caution must be exercised in interpreting and using them for policy making, until they can be confirmed independently. [ 15 ] However, there is already evidence that men are more satisfied of their clinical training in general surgery and consider more rarely to leave it, with women reporting less commonly support from the program, less access to faculty members when having difficulties, less respect from the attending, and less solidarity from peers.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are common to all physicians, including developing relationships with effective mentors, securing adequate funding for research or protected time, and paying off debt. 4 More unique to the field of interventional cardiology is the early and proactive management of the occupational hazards of the field, including radiation safety and orthopedic injuries. Young interventional cardiologists must take these issues seriously and be wary to not hasten their careers.…”
mentioning
confidence: 99%